2011
DOI: 10.1080/02786826.2010.547889
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Magnifier for Nano-CN Detection

Abstract: A new particle size magnifier (PSM) for detection of nano-CN as small as ∼1 nm in mobility diameter was developed, calibrated and tested in atmospheric measurements. The working principle of a PSM is to mix turbulently cooled sample flow with heated clean air flow saturated by the working fluid. This provides a high saturation ratio for the working fluid and activates the seed particles and grows them by condensation of the working fluid. In order to reach high saturation ratios, and thus to activate nano-CN w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
305
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 324 publications
(311 citation statements)
references
References 44 publications
5
305
0
1
Order By: Relevance
“…In our study we confirmed the calculation presented in Vanhanen et al (2011), which predicted the peak supersaturation to occur at mixing ratio of 0.1 in the mixing zone. The calibration of the nCNC in the mixing activation mode is presented in Fig.…”
Section: Operation Temperaturessupporting
confidence: 80%
See 4 more Smart Citations
“…In our study we confirmed the calculation presented in Vanhanen et al (2011), which predicted the peak supersaturation to occur at mixing ratio of 0.1 in the mixing zone. The calibration of the nCNC in the mixing activation mode is presented in Fig.…”
Section: Operation Temperaturessupporting
confidence: 80%
“…The mixing ratio in the PSM is defined as Q saturator /(Q aerosol + Q saturator ), where Q indicates a volume flow rate of a given flow. In our study the observation of Vanhanen et al (2011) is experimentally explained by two different regions of supersaturation inside the PSM.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations